1973
DOI: 10.1002/1097-0142(197301)31:1<110::aid-cncr2820310115>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating lobular carcinoma of the breast

Abstract: Three hundred and fifty‐four patients with histologically proven infiltrating lobular carcinoma of the breast were seen at Memorial Hospital, New York City, between 1956 and 1970. This comprised 5.8% of all breast cancers seen during this interval. Infiltrating lobular breast cancer is found less frequently in the Negro female—3.7% vs. 5.8% for all breast cancer. Histologic differentiation from infiltrating duct carcinoma may be difficult. Clinical diagnosis is often complicated by its gross similiarty to “loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(36 citation statements)
references
References 11 publications
(1 reference statement)
1
34
0
1
Order By: Relevance
“…Previous suggestions (Ashikari et al, 1973;Wheeler & Enterline, 1976;Nielson et al, 1986) that bilateral cancers are more frequently seen with lobular carcinomas are confirmed. A possible explanation arises from the finding of lobular carcinoma in situ (LCIS) in 66% of ipsilateral (Dixon et al, 1982) and 35% of contralateral breasts (Urban, 1967) in patients with invasive lobular carcinoma; LCIS lesions can also progress to invasive carcinoma (Haagensen et al, 1978;Rosen et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Previous suggestions (Ashikari et al, 1973;Wheeler & Enterline, 1976;Nielson et al, 1986) that bilateral cancers are more frequently seen with lobular carcinomas are confirmed. A possible explanation arises from the finding of lobular carcinoma in situ (LCIS) in 66% of ipsilateral (Dixon et al, 1982) and 35% of contralateral breasts (Urban, 1967) in patients with invasive lobular carcinoma; LCIS lesions can also progress to invasive carcinoma (Haagensen et al, 1978;Rosen et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…9 Finally, ILC has a higher incidence of bilaterality, multifocality, and multicentricity than IDC. 10 The same biologic characteristics that make ILC difficult to detect clinically or mammographically can make it harder to detect axillary lymph node metastases. 11 Nodes may remain nonpalpable even when extensively involved, and the bland-looking metastatic tumor cells may mimic histiocytes or other benign cell types.…”
mentioning
confidence: 85%
“…Some long-term follow-up studies have shown a trend to later locoregional recurrence [11]. In addition, it has been reported that ILC is less responsive to chemotherapy [3,21], lacks potential benefit of HER2 targeted therapy [16,17], being typically HER2 negative, but is more often HR positive and responsive to adjuvant hormonal therapy (HT) [11,22,23]. Reported prognosis of ILC varies and has been reported to be worse [1,9,[24][25][26][27], no different [17,[28][29][30][31][32], or better [6] than that with IDC.…”
Section: Introductionmentioning
confidence: 99%